Renovation of the levelling network of the Municipality of Ljubljana - Koler, Božo (Geodetski vestnik, 2024)
The article presents the renovation and upgrading of the urban leveling network of the municipality of Ljubljana. The old measurements in the of the municipality of Ljubljana area, the renovation project and the form of the new leveling network as well as the leveling measurement are presented. The pre-processing of the data is described. Based on the analysis of the stability of the 1st order benchmarks of the leveling network of Slovenia, the predetermined benchmarks for the adjustment of the leveling network were selected. The precision is analyzed based on the deviations of the both sides measured height differences, the deviations when closing the leveling loops and the corrections of the measured height differences after adjustment.
Keywords: adjustment; geodezija; izmera; levelling network; Ljubljana; measurement; nivelmanska mreža; precision analysis